(3NRGfI GdCTYGQs
(3ChdgG (B:s
(3CWdYJ aj Gab GdceG chGcHG CVMJ dHgLJgG GdHOhQ ZhGQHG s
(3BNQgG (B:s
(3jG ef EPG NaJ ajg GdPd Beffj Lejd EfUGag ef YPd YRGdj s
(3hgj eLehYI JTJed Ydi oeNJUQ OjhGf CHj JeGes
(3heNJUQ OjhGf cYH Hf RgjQs
(3hTYQ Wdjb GdNRGYjs
(3hoefJNHGJ ef TYQ YfJQIs
(3hWQaI Hf GdYHOs
(3hef ebUhQI GHf OQjOs
Keywords: (3GdCOHs